The First Labour Hospital (London : Co-operative Printing Society Ltd., 1921)
1921 1921 1920s 8 pages 4 and paralysis, limbs rendered useless from badly healed scars, general damage of the soft parts (muscles, tendons, etc.), interfering with usefulness, old and unreduced dislocations of joints, dislocated cartilage of the knee, fixed joints, contracted fingers or toes, arthritis, sciatica, rheumatism, rupture and general surgical complaints. The Hospital has 135 beds and a large out-patient department. TREATMENT. In addition to the Wards, we have X-Ray Department, Treatment Rooms, Operating Theatre and Baths, also Electrical Apparatus is available for use both in Treatment Rooms and Wards. By means of such apparatus, accurate diagnosis is possible of injuries to muscles and nerves. Further, by electrical stimulation the nutrition of muscles can be maintained until such times as they resume normal functions. [photograph] TREATMENT ROOM. We have a large staff of qualified men and women to carry out massage and manipulative treatment so essential to the class of work with which we deal. BENEFITS. Subscribing Members not in arrears are entitled to Treatment, Maintenance, and Conveyance to and from the Society's Hospitals, subject to local rules and conditions. Distance is no barrier. Railway Fares are paid. There is no limit. Many Patients travel over 200 miles. FINANCE. Our motto is "No Charity," and everyone working for the Hospital is remunerated. The Hospital is solvent, and has been running on its present basis for two years. 36/H24/15